Topography modifies the effect of land‐use change on soil respiration: A meta‐analysis - Yanjun Zhang; Junliang Zou; Shuina Dang; Bruce Osborne; Yuanyuan Ren; Xueliang Ju (Ecosphere, 2021)
Abstract Soil respiration is controlled by land‐use changes associated with cropland vegetation restoration, and this can vary with topography, although the magnitude of this effect and the underlying mechanisms are still unclear. We synthesized 69 recently published papers from China to explore the influence of topography‐related changes in land use on soil respiration where croplands were converted into orchards (abbreviated as C‐O), grasslands (abbreviated as C‐G), or woodlands (abbreviated as C‐W). Our results showed that not only did land‐use change have a significant influence on soil respiration, but this varied with topography. While C‐O resulted in a decrease in soil respiration by, on average, 3.1%, both the magnitude and sign of the change varied with topography, with an 8.2% increase for flat areas and a 14.7% decrease for slopes. For the C‐G conversions, soil respiration increased, on average, by 21.4%, with a 19.5% and a 24.3% increase for flat and slope topography, respectively. For C‐W, soil respiration increased, on average, by 28.0%, with only a 1.6% increase for flat areas, but a 39.9% increase for slopes. Soil temperature, soil moisture, root biomass, soil organic carbon (SOC), soil microbial biomass carbon (MBC), soil carbon‐to‐nitrogen ratio (C:N ratio), and soil density also varied with topography, with larger changes for slopes than for flat topography. Increases in soil respiration associated with different topography were closely related to changes in soil temperature, SOC, MBC, and root biomass (P < 0.05), but were not correlated with changes in soil moisture, C:N ratio, or soil density (P > 0.05). The contribution of different drivers to the change in soil respiration under different topographical conditions showed a trend of SOC > root biomass > MBC > soil temperature. Based on these results, topography‐related variations in soil respiration need to be accounted for when quantifying the impact of land‐use change on C budgets.